Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.17305/bjbms.2017.1505
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of interleukin 6, 8, and 10 between off-pump and on-pump coronary artery bypass groups

Abstract: This study aimed to evaluate the role of off-pump coronary artery bypass (CAB) surgery on the decrease of postoperative inflammatory responses in patients. We systematically searched databases of PubMed and Embase to select the related studies. Interleukin (IL) 6, 8, and 10 were used as outcomes and pooled analysis was performed using R 3.12 software. Standardized mean differences (SMDs) and their 95% confidence intervals (95% CIs) were considered as effect estimates. A total of 27 studies, including 1340 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[ 44 ] Studies evaluating proinflammatory cytokines release after OPCAB and on-pump CABG have, however, reported contradictory results. [ 45 ] There is insubstantial evidence of reduction of the postoperative systemic inflammatory reaction and platelet activation after OPCAB. [ 46 ] The Randomized On/Off Bypass (ROOBY) trial of 2203 patients, comparing Off-pump and On-pump CABG, found no significant reduction in the incidence of POCD on shunning CPB.…”
Section: Role Of Cardiac Surgerymentioning
confidence: 99%
“…[ 44 ] Studies evaluating proinflammatory cytokines release after OPCAB and on-pump CABG have, however, reported contradictory results. [ 45 ] There is insubstantial evidence of reduction of the postoperative systemic inflammatory reaction and platelet activation after OPCAB. [ 46 ] The Randomized On/Off Bypass (ROOBY) trial of 2203 patients, comparing Off-pump and On-pump CABG, found no significant reduction in the incidence of POCD on shunning CPB.…”
Section: Role Of Cardiac Surgerymentioning
confidence: 99%
“…Studies that evaluated the circulating levels of proinflammatory cytokines (IL‐6, ‐8, and ‐10) after off‐ and on‐pump‐ surgery reported contradictory results 14, 18, 19, 20, 21, 22…”
Section: Differences In Systemic Inflammatory Reaction and Platelet/cmentioning
confidence: 99%
“…These complications relate to surgical techniques, anesthesia, and cardiopulmonary bypass protocols [ 5 ]. Further, contact of blood components with the surface of the extracorporeal circuits, reperfusion injuries, endotoxemia, and surgical trauma are among the processes that can activate the pro-inflammatory system and cytokine release, mainly interleukin-6 (IL-6) during on-pump CABG [ 6 , 7 ]. IL-6 is a widely discussed biomarker in conjunction with extracorporeal circulation and inflammation during cardiac surgical interventions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%